The effectiveness of Mendong plant (Fimbrystilis globulosa) as a phytoremediator of soil contaminated with chromium of industrial waste - Pungky Ferina; Retno Rosariastuti; S Supriyadi (Brawijaya University, 2017)
The textile industry produces sideline output in the form of dangerous waste. The textile industrial waste containing heavy metal, one of which is Chromium (Cr). Chromium is very dangerous metal for environment, especially chromium hexavalent that has properties of soluble, carcinogenic, and toxic. The pollution of chromium in soil is a problem that the action to be taken with the technology of bioremediation. Phytoremediation of soil contaminated with chromium using Mendong plant (Fimbrystilis globulosa), combined with association of microorganisms Agrobacterium sp I3 and compost. This study was conducted in field experiment plots using a completely randomized block design. Data were analyzed using Anova followed by Duncan and correlation tests. The results showed that the Mendong plant was an effective phytoremediator of soil contaminated with chromium and it can be used as a chromium accumulator plant. The highest decrease of soil chromium content of 58.39% was observed on the combined artificial fertilizer, Agrobacterium sp I3 and Mendong plant treatment (P1B1T1). Removal effectiveness of chromium at the treatments using Mendong plant was higher than without the Mendong plant. Chromium uptake in shoots was higher than in roots of Mendong plant. Bioremediation increased the total bacterial colonies, decreased soil pH, and increased cation exchange capacity of the soil. The growth of the Mendong plant was in a good condition during the process of bioremediation.